Synthesis, crystal structure and Hirshfeld surface analysis of 5-methyl-1H-pyrazol-3-yl 4-nitrobenzenesulfonate at 90 K - Vinaya; Syida A. Yakuth; Thaluru M. Mohan Kumar; Besagarahally L. Bhaskar; Thayamma R. Divakara; Hemmige S. Yathirajan; Yeriyur B. Basavaraju; Sean Parkin (Acta Crystallographica Section E: Crystallographic Communications)
This study presents the synthesis, crystal structure, and a Hirshfeld-surface analysis of the bioactive compound 5-methyl-1H-pyrazol-3-yl 4-nitrobenzenesulfonate(C10H9N3O5S), a pyrazole derivative with pharmacological potential. Pyrazoles are known for diverse bioactivities, and recent research emphasizes their role as a ‘privileged structure’ in drug design. Here, the asymmetric unit of the title compound contains two distinct molecules, A and B, exhibiting differences in conformation resulting from variation in key torsion angles. These distinctions influence the molecular orientation and intermolecular interactions, with strong N—H...N and N—H...O hydrogen bonds forming a centrosymmetric tetramer stabilized by π–π stacking. Hirshfeld surface analysis readily confirms differing intermolecular contacts for A and B, primarily involving hydrogen atoms and differences in their close contacts to nitrogen and oxygen. This study offers further insight into the molecular architecture and potential interactions of pyrazole-based drug candidates.